Landscape architects in Architects’ Master Association - recultivation of the Törökugrató - Bányagödör, Budaörs - Csepely-Knorr, Luca; Lád, Gergely (4D Journal of Landscape Architecture and Garden Art, 2007)
In January 2007 the Town Council of Budaörs in conjunction with the Hungarian Architects' Master Association announced a planning competition entitled 'The Recultivation of the Area of Törökugrató- Bányagödör in Budaörs' to which students in the 19th cycle of the Master’s Course in Architecture were invited to submit entries. This call was unprecedented in the history of the Master’s school since designs were to be drawn up with the contribution of landscape architects to achieve that the two fields join forces.
Keywords: Architects' Master Association; recultivation; Budaörs